86.7k views
1 vote
If the first step of the equation -x + 6 = 5 - 3x is "subtract 5" then what should the next step be

2 Answers

2 votes

Answer:

Explanation:

all you need to do is solve for x right? so in that case when you subtract 5 from both sides you get -x+1=-3x

then you will add x on each side

you should now have 1=-2x

divide each side by -2 and then you will have

-1/2=x

User Mario J Vargas
by
5.8k points
2 votes

Answer:

The next step is add x to each side

Explanation:

-x + 6 = 5 - 3x

Subtract 5 from each side

-x + 6-5 = 5-5 - 3x

-x+1 = -3x

Add x to each side

-x+1 = -3x+x

1 = -2x

User Marius Danila
by
5.5k points